Ethnomusiological education for a humane society: ethical issues in the post-colonial, post-apartheid era - Kartomi, Margaret J. (International Library of African Music, 1999)
In this paper I want initially to discuss some ethical problems which we educators have on the whole somewhat neglected: firstly, ethical issues that need to be incorporated into the education of students of the traditional and popular musics of the world at the secondary and tertiary level in this post-colonial and post-apartheid era, and secondly, the related ethical issues affecting the work of ethnomusicologists as they study and record the musics of traditional communities throughout the world, and especially the recent transformation of field recordings made by ethnomusicologists and others into the commercial product which we know as 'world music', or music that is, or is claimed to be, based on traditional music but has been adapted to a popular musical idiom and has thereby been made 'palatable' for commercial exploitation.
Keywords: African Music